2016
DOI: 10.1371/journal.pone.0154073
|View full text |Cite
|
Sign up to set email alerts
|

Physical Workload and Work Capacity across Occupational Groups

Abstract: This study aimed to determine physical performance criteria of different occupational groups by investigating physical activity and energy expenditure in healthy Swiss employees in real-life workplaces on workdays and non-working days in relation to their aerobic capacity (VO2max). In this cross-sectional study, 337 healthy and full-time employed adults were recruited. Participants were classified (nine categories) according to the International Standard Classification of Occupations 1988 and merged into three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 30 publications
(45 reference statements)
4
31
1
2
Order By: Relevance
“…We are not aware of any other large-scale investigation examining a combination of several health risk indicators in different high-resolution occupational groups. Though, the physical activity patterns at work and in leisure time in the present study are partly similar to previous reports in both major occupational groups and in some sub-major groups (9,10,21). For example, white collar/professional occupations are consistently reported to have a higher amount of leisure time moderate-to-vigorous physical activity compare to blue collar workers (4,21), with less differences in leisure time sitting (22,23).…”
Section: Single Risk Indicators In Occupational Groupssupporting
confidence: 89%
See 1 more Smart Citation
“…We are not aware of any other large-scale investigation examining a combination of several health risk indicators in different high-resolution occupational groups. Though, the physical activity patterns at work and in leisure time in the present study are partly similar to previous reports in both major occupational groups and in some sub-major groups (9,10,21). For example, white collar/professional occupations are consistently reported to have a higher amount of leisure time moderate-to-vigorous physical activity compare to blue collar workers (4,21), with less differences in leisure time sitting (22,23).…”
Section: Single Risk Indicators In Occupational Groupssupporting
confidence: 89%
“…As these are heterogeneous groups of occupations with a diversity of work situations that could have an effect on health outcomes. For instance, previous reports have indicated variations in overweight, smoking and occupational physical activity between a larger range of occupational groups (9,10,8). Other studies found differences in physical activity but con icting results of cardiorespiratory tness between occupational groups (9,11).…”
Section: Introductionmentioning
confidence: 97%
“…One study found Swiss workers with manual jobs (e.g. craftsmen, machine operators and labourers) to be more active on workdays than non-workdays [37]. Another study reported adults with low educational level as less likely to be active during the weekend (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The VO 2 max can be estimated applying a specific equation [85]. It has been used to asses cardiorespiratory fitness in several studies [86,87].…”
Section: Indirect Field Testsmentioning
confidence: 99%